Bittersweet memories and somatic marker hypothesis: adaptive control in emotional recall facilitates long-term decision-making in the Iowa Gambling Task - Singh, Varsha (Frontiers in Neuroscience, 2024)
The somatic marker hypothesis states that emotion recall and its somatic influence guide longterm decision-making; however, the mechanism through which decision-making benefits from emotion recall is unclear. Whether emotion recall and the induced affect increases the regulatory demand or amplifies the affect state that requires inhibition. It is unclear if controlling the automatic flow of emotion in recall improves adaptive decision-making. The two studies examine the hypothesis that affect control in emotion recall facilitates inhibitory control and benefits longterm decision-making. In Experiment 1 (n = 137), affect control was assessed in emotion recall counterbalanced for order of positive and negative emotion; emotion recall sequences (positive−negative recall vs. negative−positive recall) were expected to engage affect control and benefit long-term decision-making. Results for long-term decision-making showed that negative−positive recall sequence was associated with higher long-term decision making, whereas the results of frequency decision-making showed no effect of the emotion recall sequence. In experiment 2 (n= 71, all male), emotion recall (positive vs. negative), recall specificity (i.e., specific vs. overgeneralized recall), and post-recall mood regulation (post-recall positive mood regulation vs. no regulation) was expected to facilitate long-term decision-making. Results showed that emotion recall and post-recall mood regulation (i.e., negative recall -positive mood and positive recall -negative mood) were associated with higher long-term decision-making. Results of frequency decision-making showed that positive emotion recall, and poor recall specificity led to infrequent punishment deck choices. Hierarchical regression indicated that emotion recall increased infrequent deck choices and accounted for 10% of choices made, recall specificity increased the explanatory power to 19 % and higher recall specificity was associated with fewer infrequent punishment deck choices. Affect control engaged via negative emotion recall, post-AFFECT CONTROL AND DECISION-MAKING 3 recall mood regulation, and recall specificity might be a potential mechanism through which affect control in emotion recall might facilitate long-term decision-making.